2022
DOI: 10.3390/molecules27010287
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-Diabetic Activities and UHPLC-ESI-MS/MS Profile of Muntingia calabura Leaves Extract

Abstract: Anti-diabetic compounds from natural sources are now being preferred to prevent or treat diabetes due to adverse effects of synthetic drugs. The decoction of Muntingia calabura leaves was traditionally consumed for diabetes treatment. However, there has not been any published data currently available on the processing effects on this plant’s biological activity and phytochemical profile. Therefore, this study aims to evaluate the effect of three drying methods (freeze-drying (FD), air-drying (AD), and oven-dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 55 publications
0
28
0
1
Order By: Relevance
“…In a previous study, a total of sixty-one compounds were tentatively identified in the MC extract through UHPLC-ESI-MS/MS analysis, including geniposide, daidzein, quercitrin, kaempferol, formononetin, and 6-hydroxyflavanone [12]. These six available standards were then quantitated in the MC extract by UHPLC analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study, a total of sixty-one compounds were tentatively identified in the MC extract through UHPLC-ESI-MS/MS analysis, including geniposide, daidzein, quercitrin, kaempferol, formononetin, and 6-hydroxyflavanone [12]. These six available standards were then quantitated in the MC extract by UHPLC analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Upon examination of the S-plot (Fig. 8B), glucose (20), allantoin (10), hippurate (22), methylnicotinamide (1), citrate (13), lactate (25), pyruvate (32), dimethylamine (17), hydroxybutyrate (3), trigonelline (35) and aconitate (12) were the prominent metabolites with strong correlation that contributed to the discrimination of the DC group from 13 This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dried sponge usually has a sweet taste and a crunchy texture [5]. There are many dry sponges on the market, but the dry cakes found in the market generally only use pandan leaves as a colorant and aroma enhancer [6]. In this case the author wants to add a variety of other raw materials in the manufacture of dry sponge cake, but it has great benefits [7].…”
Section: Introductionmentioning
confidence: 99%